Digital terrain model extraction using digital aerial imagery of unmanned aerial vehicle - Udin, Wani Sofia (IEEE, 2012)
Digital Terrain Model (DTM) is extensively applied in various fields such as surveying and construction engineering, natural disaster management system, structure monitoring, and many more. Generally, the demand on accuracy and very detail information of DTM extraction is crucial for most of the applications. The advancement of photogrammetry and spin-off technology has advantageous in extracting highly accurate DTM. Currently, the DTM can be extracted from digital aerial imagery of small format camera mounted on light weight platform such as Unmanned Aerial Vehicle (UAV). The study is performs to assess the accuracy of DTM derived from UAV platform. Canon PENTAX W90 is utilized as non-metric camera for the earth information acquisition. In this study, 23 points of three dimensional coordinates (3D) were established using real time kinematic Global Positioning System (RTK-GPS) technique. Sixteen points are used in ground control point (GCP) for the purposes of aerial triangulation while seven as check point (CP) for accuracy assessment. The research output is then evaluated for planimetry and vertical accuracy using root mean square error (RMSE). Based on the analysis, sub-meter accuracy is obtained. As conclusion, UAV digital imagery can be used for accurate applications.